MIDWIFERY CARE FOR MOTHER “CN” AGE 20 YEARS PRIMIGRAVIDA FROM 18 WEEKS 3 OF PREGNANCYDAY TO 42 DAYS OF POST-OFF PERIOD Case Study Conducted at the Implementing Unit of Petang I Health Center in 2025 - Widiastrini, Ni Wayan; Astiti , Ni Komang Erny (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Continuous and all-encompassing midwifery care is the best option for moms and their newborns. The Implementing Unit of Petang I Health Centre offered midwifery care to moms "CN" from 18 weeks and 3 days of pregnancy to 42 days postpartum from October 2024 to April 2025. The data collection method is primary data through interviews, examinations and observations while secondary data from documentation. Midwifery care for pregnancy is in accordance with the 10 T midwifery service standards with complementary care for pregnant women’s classes with pregnancy exercises and gymballs. The results of midwifery care during pregnancy are physiological. Assistance for mothers giving birth with Normal Delivery Care standards and complementary care effleurage massage. The mother gave birth vaginally with an episiotomy without complications. Stage I lasted for 3 hours, stage II 40 minutes, stage III 7 minutes and monitoring of stage IV results were within normal limits. Neonatal midwifery care with essential neonatal health service standards. The baby was born normally and received complementary care of baby massage, neonatal midwifery care was physiological. The postpartum period was normal with complementary care of Kegel exercises and oxytocin massage, the mother used IUD contraception. The care given to mother "CN" has been given in accordance with standards in a comprehensive and continuous manner.